2014
DOI: 10.1189/jlb.3ma0114-034rr
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 inhibition during the hypoinflammatory phenotype of sepsis enhances immunity and improves outcome

Abstract: Mechanism-based sepsis treatments are unavailable, and their incidence is rising worldwide. Deaths occur during the early acute phase of hyperinflammation or subsequent postacute hypoinflammatory phase with sustained organ failure. The acute sepsis phase shifts rapidly, and multiple attempts to treat early excessive inflammation have uniformly failed. We reported in a sepsis cell model and human sepsis blood leukocytes that nuclear NAD+ sensor SIRT1 deacetylase remodels chromatin at specific gene sets to switc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
188
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 114 publications
(205 citation statements)
references
References 43 publications
13
188
2
Order By: Relevance
“…Remarkably, we found in mice that inhibiting SIRT1 activity after the switch to adaptation improves peripheral circulation, restores immune competence, and markedly improves survival (20). That study, however, did not address whether SIRT1 inhibition rebalanced glucose and fatty acid mitochondrial oxidation or altered mitochondrial bioenergetics.…”
mentioning
confidence: 74%
See 4 more Smart Citations
“…Remarkably, we found in mice that inhibiting SIRT1 activity after the switch to adaptation improves peripheral circulation, restores immune competence, and markedly improves survival (20). That study, however, did not address whether SIRT1 inhibition rebalanced glucose and fatty acid mitochondrial oxidation or altered mitochondrial bioenergetics.…”
mentioning
confidence: 74%
“…Using our established model of murine sepsis (cecal ligation and puncture) (20), we found that treating sepsis splenocytes ex vivo for 24 h with the SIRT1 inhibitor EX-527 significantly decreased mRNA levels of Relb, Sirt3, Idh 2 , Sod 2 , and Vdac (Fig. 8D).…”
Section: Sirt1 Controls Bioenergy Shifts In Normal and Sepsis-adaptedmentioning
confidence: 99%
See 3 more Smart Citations